Assessing the relevance of self-reported ADHD symptoms and cognitive functioning for psychopathy using the PCL-R and the TriPM. Issue 4 (4th July 2019) - Pauli, Malin; Liljeberg, Jenny; Gustavsson, Petter; Kristiansson, Marianne; Howner, Katarina
ABSTRACT: Psychopathy and ADHD are highly comorbid disorders, possibly linked to the underlying trait of impulsivity. It is therefore likely that ADHD symptoms are also of importance when studying cognitive functioning linked to psychopathy. Few studies of psychopathy and cognitive functioning have taken ADHD symptoms into account. In this cross-sectional study, male offenders (n = 201 of whom 105 were neuropsychologically tested) were recruited from all high security correctional facilities in Sweden. The aim of the study was to investigate if self-reported ADHD symptoms and cognitive functioning could predict specific subcomponents of psychopathy in offenders. Results showed that self-rated ADHD symptoms (ASRS) and psychopathy were highly correlated. Furthermore, the associations of ASRS and PCL-R Facet 3, as well as TriPM Disinhibition, were remarkably high. As expected, ASRS was not related to either Facet 1 or 2 of the PCL-R, or to TriPM Boldness. Cognitive functioning did not contribute in predicting psychopathy beyond the effect of ASRS. The high overlap in reported symptoms highlights the importance of thorough clinical assessments to be able to distinguish psychopathic personality traits from ADHD and lessen the risk of misdiagnosis. Further, it points to the need of finding discriminative measures possibly linked to etiological underpinnings.